2014
DOI: 10.1016/j.evalprogplan.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Implementation assessment of widely used but understudied prevention programs: An illustration from the Common Sense Parenting trial

Abstract: Common Sense Parenting is a parent-training program that is widely disseminated, has promising preliminary support, and is being tested in a randomized controlled trial that targets lower-income, urban 8th-grade students and their families (recruited in two annual cohorts) to improve the transition to high school. The workshop-based program is being tested in both standard 6-session (CSP) and modified 8-session (CSP Plus) formats; CSP Plus adds adolescent-skills training activities. To offer a comprehensive pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The CSP Plus sessions adopted the same structure as CSP and included new content on goal setting for parents and teens in relation to the transition to high school and guided skills practice in family communication and decision making regarding the opportunities and responsibilities involved in this transition. Fidelity assessments conducted by coding a random sample of videotaped workshop sessions with 96% agreement across two independent raters indicated that 95% of the core components of the interventions were delivered as designed (Oats, Cross, Mason, Casey-Goldstein, Haggerty, & Hanson, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…The CSP Plus sessions adopted the same structure as CSP and included new content on goal setting for parents and teens in relation to the transition to high school and guided skills practice in family communication and decision making regarding the opportunities and responsibilities involved in this transition. Fidelity assessments conducted by coding a random sample of videotaped workshop sessions with 96% agreement across two independent raters indicated that 95% of the core components of the interventions were delivered as designed (Oats, Cross, Mason, Casey-Goldstein, Haggerty, & Hanson, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…The two raters’ overall quality scores for each session were strongly correlated ( r = .70, p < .001). Inquiries regarding the full quality form may be made to the first author or first author of Oats et al (2014), and dissemination would be at the discretion of Boys Town.…”
Section: Methodsmentioning
confidence: 99%
“…Time was recorded on a time form by the viewing rater, who wrote down the time-stamps on the video recordings. The objective nature of the time-stamp data made double-coding unnecessary for time adherence calculation (see Oats et al, 2014). CSP and CSP Plus delineate specific time parameters for each component; however, adherence to the time limits is not recorded as part of model adherence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations